Synthesis of six-membered silacycles by borane-catalyzed double sila-Friedel–Crafts reaction - Dong, Yafang; Sakai, Masahiko; Fuji, Kazuto; Sekine, Kohei; Kuninobu, Yoichiro (Beilstein Journal of Organic Chemistry, 2020)
We have developed a catalytic synthetic method to prepare phenoxasilins. A borane-catalyzed double sila-Friedel–Crafts reaction between amino group-containing diaryl ethers and dihydrosilanes can be used to prepare a variety of phenoxasilin derivatives in good to excellent yields. The optimized reaction conditions were also applicable for diaryl thioethers to afford their corresponding six-membered silacyclic products. The gram-scale synthesis of a representative bis(dimethylamino)phenoxasilin and the transformation of its amino groups have also been demonstrated.
Keywords: borane; cyclic compound; organosilane; sila-Friedel–Crafts; silylation